Identification and validation of key mitophagy-related biomarkers in the pathogenesis of proliferative diabetic retinopathy - Liu, Yifan; Zhou, Ye; Chen, Jie; Jin, Jiahui; Wang, Xueying; Wang, Xi; Zhang, Jieping; Li, Jiao; Zhang, Junfang; Zhu, Ling; Xu, Guo-Tong; Bi, Yanlong; et al. (Frontiers in Endocrinology, 2025)
IntroductionDiabetic retinopathy (DR) is one of the most common microvascular complications of diabetes mellitus, and proliferative diabetic retinopathy (PDR) represents its advanced stage. The etiology of PDR is complex. Mitophagy, the selective degradation of dysfunctional mitochondria, is crucial for cellular homeostasis and has been implicated in PDR pathogenesis. However, its specific mechanisms require further investigation.Materials and methodsGene Expression Omnibu (GEO) datasets (GSE102485, GSE60436) were analyzed in R software to identify differentially expressed mitophagy-related genes (DEMRGs). A PDR diagnostic model was constructed by gene ontology (GO) enrichment analysis, genome enrichment analysis (GSEA), and other relevant methods. Immune infiltration was also performed to analyze the changes in immune cells. Finally, the retinal pigment epithelial cell line (ARPE-19) was incubated with high glucose (HG) to simulate a DR model in vitro, hub-gene expression and mitophagy were assessed by qRT-PCR, Western blotting, and immunofluorescence microscopy (IF).ResultsEight DEMRGs were identified enabling construction of a PDR diagnostic model and prioritization of two hub genes (CASP8 and COL1A1). Finally, qRT-PCR, Western blotting, and IF were performed to provide preliminary validation of the PDR model and HG stimulation increased mitochondria–lysosome colocalization as well as enhanced the expression of mitophagy-related proteins.ConclusionIntegrated bioinformatics and experimental validation suggest that mitophagy contributes to PDR pathogenesis. Five DEMRGs showed up-regulated and immune cell infiltration that may affect the occurrence and PDR development by regulating mitophagy. These findings provide candidate biomarkers and mechanistic insight into PDR.